The Inauthenticity Problem of Human Being in Russian Philosophy - Usachyov, Alexander V. (Journal of History Culture and Art Research, 2020)
The study discusses the problem of inauthentic human being (existence) in modern world based on Russian religious philosophy works included in the curriculum. The study uses a comparative and analytical approach, on the basis of which the ideas of European philosophy are compared with the thoughts of Russian authors. This comparison helps to create a discussion field where the problem of human inauthenticity can be clarified and verified. According to Russian philosophers, there are certain provisions in Western philosophy, which state that the perception of a human as a separate kind of being among other beings leads to the loss of traits that are decisive in many aspects of the human existence. The study aims to justify these provisions. The study presents all stages of comparing Russian and Western philosophy’s understanding of a human, which are related to the formation of a concept that underlies the anthropology of ideal-realism. This concept establishes in great detail that human can be considered only from the standpoint of an organic worldview and outside of an abstract approach that exaggerates one of the aspects of human being. The research results are novel and have a practical significance for a detailed analysis of human being and the inauthenticity problem. The study defines the problem, its semantic boundaries, and the set of concepts and categories, within which the problem is outlined. The study also determines that the problem can be solved at the level of statements and intuitions. The statement of the purpose is heuristic and may contain forecasts and perspective conclusions based on the analysis of human being, the relevance of which today is all too clear. The identification of the human being’s essential features will help us understand why many concepts interpret the existence one-sidedly, abstractly, without considering other important aspects.